Implementasi Strategi Budaya “Ayo Sekolah” dalam Mewujudkan Tujuan Pendidikan Nasional melalui Keterlibatan SMPN 3 Gempol Satu Atap pada Masyarakat Desa Wonosunyo Kecamatan Gempol Kabupaten Pasuruan - Yenni Febrianti; Siti Awaliyah; A. Rosyid Al Atok (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2026)
The research aims to describe the implementation of the "let's go to school" cultural strategy in realizing national education goals through the involvement of SMPN 3 Gempol One Roof in the community in Wonosunyo Village, Gempol District, Pasuruan Regency. The focus of this research is the implementation of the "let's go to school" cultural strategy. This research uses a qualitative approach with descriptive research type. The informants for this research were 5 people, namely teachers, students and the community. Data collection techniques in this research are structured interviews and documentation. Interview data will be analyzed by means of data reduction, data presentation, and drawing conclusions. The results of this research show that through outreach which is not only carried out by word of mouth, but through outreach, distributing brochures and posters inviting people to go to school, this can change people's mindset so that they are aware that education is mandatory for up to 12 years and is important for the future.